Pengaruh Job Insecurity dan Kepemimpinan Visioner terhadap Kinerja Karyawan Dimoderasi Kepuasan Kerja pada PT Mega Indah Sari - Syahnur, Ikka (Study of Scientific and Behavioral Management, 2024)
ABSTRACTThis research aims to determine the effect of job insecurity and visionary leadership on employee performance moderated by job satisfaction at PT Mega Indah Sari. In this research, the variables used are job insecurity and visionary leadership as independent variables, performance as the dependent variable, and job satisfaction as the moderating variable. This research is quantitative research. The data source used in this research is primary data collected through a survey using a questionnaire. The method for calculating the number of samples uses the Slovin formula and the sampling technique uses probability sampling, so the number of samples used is 110 people. Data is processed using the Patrial Least Squares (PLS) method and applied using Smart PLS 4. The results of this study show that job insecurity has a positive and insignificant effect on employee performance, visionary leadership has a positive and significant effect on employee performance, job insecurity has a positive and significant effect on employee performance which is moderated by job satisfaction, and visionary leadership has a negative and significant effect on employee performance. . which is moderated by job satisfaction. Keywords: Job insecurity; visionary leadership; employee performance; job satisfaction